2022
DOI: 10.3389/fped.2022.876791
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Mathieu Urethroplasty vs. Tubularized Incised Plate Urethroplasty for the Management of Distal Penile Hypospadias With a Small Glans

Abstract: IntroductionDistal hypospadias is a common anomaly. Different surgical techniques have evolved through the years to manage this anomaly. Several factors may affect the prognosis. One of them is glans size. We compared the hybrid Mathieu urethroplasty (HMU) and the tubularized incised plate urethroplasty (TIPU) for the management of distal hypospadias with a small glans.MethodsSixty-eight patients with distal hypospadias were included and categorized into two groups. Group A (n = 33) and group B (n = 35) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…12 Some authors have reported that if the Mathieu technique includes incision of the urethral plate, then it may be superior to the TIP technique for patients with small glans. 15 The Duckett technique, also known as transverse preputial island flap urethroplasty, utilises the inner preputial tissue to create the neourethra, while the axial vascular pedicle remains attached to the dorsal layer of the prepuce. 16 This method is technically demanding and results in a complication rate higher than that of the TIP and the Onlay Island flap techniques.…”
Section: Discussionmentioning
confidence: 99%
“…12 Some authors have reported that if the Mathieu technique includes incision of the urethral plate, then it may be superior to the TIP technique for patients with small glans. 15 The Duckett technique, also known as transverse preputial island flap urethroplasty, utilises the inner preputial tissue to create the neourethra, while the axial vascular pedicle remains attached to the dorsal layer of the prepuce. 16 This method is technically demanding and results in a complication rate higher than that of the TIP and the Onlay Island flap techniques.…”
Section: Discussionmentioning
confidence: 99%